Nutritional support in critical patients in the Intensive Care Unit. - Gutiérrez-Plaza , J.P.; 1 Barbosa-Rivas, F.A.; Guzmán-, Daniel H.; Cárdenas-Cortés , A.M.; Niño-Castañeda , M. S.,3; Moran-Martínez , J.; Betancourt-Martínez , N.D.; Esquivel-Franco, C.G.* (Revista de Ciencias Médicas Torreón, 2026)
Nutritional support (NS) refers to the provision of nutrientsenterally or parenterally with the purpose of maintaining anadequate nutritional status in critically ill patients in whomnormal nutrition is not possible. The patient who is admittedto the Intensive Care Unit (ICU) presents an alteration in avital organ and various metabolic disorders that lead torequiring more energy and protein, deterioration of theimmune system, body composition and gastrointestinalfunction. Nutritional support is administered to patients bynursing staff. A systematic review was carried out with themethodology of Holly Salmond and Saimbert, the eligibilitycriteria were applied, which were with the PIO question(Problem, Intervention and Results). With a bibliographicsearch analysis period it was during the year 2022. ThePRISMA methodology was applied. This study identifies thatthe nutritional support of patients in critical condition is veryimportant for the favorable evolution of their health status,starting early as an added treatment. To date, there is nogeneral caloric contribution for patients in critical condition.serious since very important parameters such as thepathology and the general state of health of the patient haveto be evaluated; However, the route of administration is oneof the variables since both require specific nursing care inadministration.
Keywords: Critical patient, nutrition, nutritional support.